Analisis Kadar HMF (Hidroxy Methyl Furfural) pada Madu Bone - Zakaria, Zakaria (Al-Kimia, 2014)
This study aimed to determine the concentration of HMF ((hydroxy methyl furfural) in Bone honey. Regency Bone with 145.073 ha of forest, of area 4,559 km² honey potential for livestock development. The quality of honey is determined from the nectar source, geographic location, and the processing technology. HMF concentration is one of the indicators in honey to determine the quality marker and freshness of honey. This research was done in three stages, namely the stage of sample preparation, extraction phase, and phase identification. Stages of sample preparation were performed to determine sampling locations, the determination of the location of the extraction and identification. Extraction is done in analytical chemistry laboratorium Science Faculty, Hasanuddin University. Honey samples were extracted with methanol. The identification process carried out in an integrated laboratory Department of Chemical Science Faculty of Hasanuddin University to obtain the data of UV-Vis, HPLC performed while the data in an integrated laboratory public health, Hasanuddin University. The results obtained by HPLC showed the data HMF concentration of 0.264 mg/kg, while the data obtained by UV-Vis HMF concentration of 0.230 mg/kg. Based on these data concluded that honey Bone has a good quality in terms of content HMF.